Tradisi Suwuk dalam Tinjauan Sains Modern - Achmad Zuhdi Dh (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2018)
For Javanese, one way to cure the sick is to do suwuk (jampi). Suwuk tradition, namely healing by reciting mantras (certain readings) that are blown on the crown of the patient and sometimes also use water media, especially for some modern Muslims, was initially seen as a healing practice that contains elements of shirk because it was considered not in accordance with the principles of Islamic 'aqīdah. Today, this view begins to change after a normative source has been found from a number of traditions that allow ruqyah that works similar to suwuk. It was also strengthened by the results of experiments and the findings of a number of scientists about the effect of certain readings and the wonders of water. This article will explain the tradition of suwuk which is the same as ruqyah, then elaborate normative sources of the Qur’ān and the Ḥadīth which legalize it and the view of modern science that supports it, so that its existence is still relevant to modernity.